Exploring the Complex Relationship Between Antidepressants, Depression and Neurocognitive Disorders - Monica Neațu; Iulia Ioniță; Ana Jugurt; Eugenia Irene Davidescu; Bogdan Ovidiu Popescu (Biomedicines)
The coexistence of dementia and depression in older populations presents a complex clinical challenge, with each condition often exacerbating the other. Cognitive decline can intensify mood disturbances, and untreated or recurring depression accelerates neurodegenerative processes. As depression is a recognized risk factor for dementia, it is crucial to address both conditions concurrently to prevent further deterioration. Antidepressants are frequently used to manage depression in dementia patients, with some studies suggesting they offer neuroprotective benefits. These benefits include promoting neurogenesis, enhancing synaptic plasticity, and reducing neuroinflammation, potentially slowing cognitive decline. Additionally, antidepressants have shown promise in addressing Alzheimer’s-related pathologies by reducing amyloid-beta accumulation and tau hyperphosphorylation. However, treatment-resistant depression remains a significant challenge, particularly in older adults with cognitive impairment. Many do not respond well to standard antidepressant therapies due to advanced neurodegenerative changes. Conflicting findings from studies add to the uncertainty, with some research suggesting that antidepressants may increase dementia risk, especially when used in patients with undiagnosed early-stage dementia. This article aims to explore the intricate relationship between depression and dementia, examining the benefits and risks of antidepressant use. We highlight the urgent need for personalized, comprehensive treatment strategies that balance mental health improvement with cognitive protection.